Low-Dose Cisplatin-Etoposide Regimen for Patients with Optic Pathway Glioma: A Report of Four Cases and Literature Review - Cardellicchio, Stefania; Bacci, Giacomo; Farina, Silvia; Genitori, Lorenzo; Massimino, Maura; de Martino, Maurizio; Caputo, Roberto; Sardi, Iacopo (Neuropediatrics, 2014)
Optic pathway gliomas (OPGs) account for 5% of all childhood brain tumors. For years it has been discussed which was the best method of examining tumor progression when the magnetic resonance imaging (MRI) scan does not change. The role of chemotherapy in their treatment still remains controversial. We treated four consecutive patients affected by progressive OPG with lower cumulative doses of cisplatin/etoposide. The extension of disease was assessed by brain MRI scan. A complete ophthalmologic examination was performed. Ototoxicity was monitored. Our OPG patients had reduced visual acuity (VA) and/or visual field (VF) regardless of the MRI evaluation. All patients showed rapid visual recovery with improvement both in VA and in VF. At the time of writing, after a median follow-up of 34 months, all patients were alive and free from disease progression. Our results confirm the effectiveness and the low-toxicity profile of the cisplatin/etoposide regimen for treatment of children affected by OPG. We suggest that VA and VF can be considered as the most accurate parameters for defining the start of chemotherapy and tumor response.
Keywords: low-grade glioma; optic pathways; brain tumors; chemotherapy; visual acuity; visual field